WAS NAPOLEON'S INVASION A REAL THREAT TO RUSSIA TO LOSE ITS NATIONAL SOVEREIGNTY? - G. Voskoboynikov, Sergey; V. Schukina, Tatyana; G. Tahtamishev, Vladimir; S. Akisheva, Maria; Y. Gumenyuk, Andrey; V. Yushina, Svetlana (Gênero & Direito, 2020)
In this article, the authors try to find the answer to the question of what consequences could have the defeat in the First Patriotic War with Napoleon in 1812. In the search for an answer to this question, the authors conclude that Napoleon’s plans in 1812 regarding Russia should be considered as part of his more general plan to create new Europe, where France was to play a leading role. This policy of Napoleon came into direct conflict with Russia’s ally, England, which also nurtured the ideas of continental hegemony. In the eyes of Napoleon, our country possessed an ambivalent essence, synthesizing in itself the West and the East, Europe and Asia, barbarism and civilization. His intentions, therefore, were to simplify the sociocultural space of Russia. For these purposes, it was proposed to separate the western regions of Russia to include them in the Europe project and gradually weaken the remaining territory of the state.